Critical current density and current distribution in field cooled superconducting disks. (31st May 2016) - Bernstein, Pierre; Noudem, Jacques; Dupont, Louis
Abstract: Applications of bulk superconductors concern superconducting motors and generators, the levitation of vehicles, the generation of high magnetic fields with small size cryo-magnets, the shielding of magnetic fields and other applications. For all of them, it is essential to determine the critical current density, and to understand the effect of the shape and size of the bulks on the properties of interest. In this contribution, we show how the combination of levitation force and trapped field measurements allow one to determine the characteristics and the potential performances of superconducting disks using analytical modeling. As examples of applications we detail the effects of the magnetizing field and of the bulk sheet critical current density on the levitation force. An important result of the reported measurements is that in field-cooled samples, the shielding currents possibly do not flow along the whole thickness of the disks.